Estudio prospectivo del impacto ambiental y su influencia en Centro de aprovechamiento de residuos sólidos y relleno sanitario de Guaranda, periodo noviembre 2022- febrero 2023. - Miranda Pazmiño, Jefferson Rubén (2023)
The work is of a qualitative nature, it consisted of carrying out a prospective study of the environmental impact and its influence on the Solid Waste Use Center of the city of Guaranda, through a diagnosis of the current situation that allowed describing a prospective of said center to propose strategies for adequate management of the environmental impact in the area. The MIC MAC software was used where the study variables were entered to determine the relationships between variables, interviews were applied to the population of the cantons of Guaranda, Chimbo, San Miguel and Chillanes that make up the community where a convenience sampling was used. or intentional. The results of this work allowed us to know if the public knows about the association for Solid Waste Management, where the benefits of having a solid waste utilization center will be built, to know what the future potential of this would be. The most influential variables were determined in the set of participants, which allowed us to establish a negative, a trend and a positive evaluation, in short, to establish a prospective, knowing the variables on which priority intervention should be made to keep the center in good working order. With this knowledge, a proposal of strategies is made for an adequate management of the center for the use of solid waste. Key words: Contamination, Impact, Solid Waste, Mitigate, Commonwealth.